A temporal shift of the evolutionary principle shaping intratumor heterogeneity in colorectal cancer - Tomoko Saito (Nature Portfolio, 2018)
Advanced colorectal cancers are characterised by intra-tumour heterogeneity dictated by neutral evolution. Here the authors analyse early colorectal tumours by whole-exome sequencing and find that Darwinian evolution determines the fate of early lesions in colorectal adenoma and carcinoma in situ.